80.3k views
3 votes
Solve the equation a = m – n for the variable n

2 Answers

1 vote

Answer:

a=m-n

(Add n to both sides)

a+n=m-n+n

(The -n and +n cancel out, on the right side of the equation)

a+n=m

(Now subtract a from both sides)

a+n-a=m+a

(The +a and -a cancel out, on the right side of the equation)

n=m+a

User Handloomweaver
by
4.4k points
5 votes

Answer:


\huge \boxed{n=-a+m}

Explanation:


a=m-n

Adding
n to both sides.


a+n=m-n+n


a+n=m

Subtracting
a from both sides.


a+n-a=m-a


n=m-a

User Gennine
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.